Edukasi pencegahan tuberculosis pada anak sekolah melalui video TOSS TBC di SMK PGRI Pangkalpinang - Lana Sari; Monia Agni Wiyatami; Dela Lanaya; Eva Dewi Rosmawati Purba; Merynda Nur Sandi; M. Seto Sudirman (INDRA: Jurnal Pengabdian kepada Masyarakat, 2026)
Tuberculosis is an infectious disease caused by the Mycobacterium tuberculosis. Around 89% of TBC cases occur in adults (56.5% in men and 32.5% in women), and 11% occur in children. Based on BPS (2023) data, the estimated TBC incidence in Bangka Belitung Province reached 6,797 cases, with the highest mortality rate found in East Belitung Regency at 11%, followed by Bangka Regency at 9%. Based on Dinkes (2024) data, from January to September, 2,136 patients were treated across the Bangka Belitung Province, indicating the need for joint efforts to reduce TBC cases. The partners for this activity are students of SMK PGRI Pangkalpinang. The activity was carried out on July 22nd, 2025. The method used was an educational counseling model using an educational video. Video media is highly engaging for delivering information about TBC because it can foster students’ interest, motivation, and enthusiasm. The study results showed a significant difference in knowledge before and after providing TBC education via video, with a p-value of 0.001 (< 0.05).